Caspase-Mediated Apoptosis in Sensory Neurons of Cultured Dorsal Root Ganglia in Adult Mouse - Hamid Reza Momeni; Malek Soleimani Mehranjani; Mohammad Ali Shariatzadeh; Mahnaz Haddadi (Cell Journal, 2013)
Objective: Sensory neurons in dorsal root ganglia (DRG) undergo apoptosis after peripheral nerve injury. The aim of this study was to investigate sensory neuron death and the mechanism involved in the death of these neurons in cultured DRG.Materials and Methods: In this experimental study, L5 DRG from adult mouse were dissected and incubated in culture medium for 24, 48, 72 and 96 hours. Freshly dissected and cultured DRG were then fixed and sectioned using a cryostat. Morphological and biochemical features of apoptosis were investigated using fluorescent staining (Propidium iodide and Hoechst 33342) and the terminal Deoxynucleotide transferase dUTP nick end labeling (TUNEL) method respectively. To study the role of caspases, general caspase inhibitor (Z-VAD.fmk, 100 μM) and immunohistochemistry for activated caspase-3 were used.Results: After 24, 48, 72 and 96 hours in culture, sensory neurons not only displayed morphological features of apoptosis but also they appeared TUNEL positive. The application of Z-VAD.fmk inhibited apoptosis in these neurons over the same time period. In addition, intense activated caspase-3 immunoreactivity was found both in the cytoplasm and the nuclei of these neurons after 24 and 48 hours.Conclusion: Results of the present study show caspase-dependent apoptosis in the sensory neurons of cultured DRG from adult mouse.